Typical characteristics of children with congenital adrenal hyperplasia due to 11β-hydroxylase deficiency: a single-centre experience and review of the literature - Breil, Thomas; Yakovenko, Vira; Inta, Ioana; Choukair, Daniela; Klose, Daniela; Mittnacht, Janna; Alrajab, Abdulsattar; Grulich-Henn, Jürgen; Bettendorf, Markus (The journal of pediatric endocrinology and metabolism, 2019)
Background: 11β-hydroxylase deficiency (11βOHD) is a rare disease representing the second most common cause of congenital adrenal hyperplasia (CAH) (5–8%) with an incidence of about 1:100,000. In contrast to 21-hydroxylase deficiency (21OHD), 11βOHD is not included in neonatal screening programmes. The objective of this study was to demonstrate the typical features of male patients with 11βOHD. Methods: Clinical, biochemical and radiological data of patients with 11βOHD were analysed in this retrospective single-centre analysis. Results: Six male patients of four unrelated families with 11βOHD were identified (0.1–13.5 years of chronological age [CA] at diagnosis). The predominant symptoms were arterial hypertension, tall stature and precocious pseudopuberty. Bone ages (BAs) were remarkably advanced at diagnosis in four index patients (median difference BA–CA: 5.5 years, range 1.5–9.2 years). Homozygous mutations were identified in exon 7 (c.1179_1180dupGA [p.Asn394Argfs*37]) and exon 8 (c.1398+2T>C) of the CYP11B1 gene leading both to a complete loss of function. The latter mutation has not yet been described in databases. 11βOHD was identified by the measurement of 11-deoxycortisol in a newborn screening card of one patient retrospectively. Testicular adrenal rest tumours (TARTs) were detected in three patients at 3.7 years, 11 years and 14.4 years. Conclusion: The diagnosis of CAH due to 11βOHD is delayed and should be suspected in children with arterial hypertension, tall stature and precocious pseudopuberty. Patients may develop TARTs as early as infancy. 11βOHD should be included in newborn screening programmes, at least in newborns of index families, to allow early diagnosis and the start of treatment to reduce morbidity.
Gesehen am 03.06.2019